CARMA1-mediated NF-κB and JNK activation in lymphocytes - Blonska, Marzenna (2009)
Activation of transcription factor nuclear factor-κB (NF-κB) and Jun N-terminal kinase (JNK) play the pivotal roles in regulation of lymphocyte activation and proliferation. Deregulation of these signaling pathways leads to inappropriate immune response and contributes to the development of leukemia/lymphoma. The scaffold protein CARMA1 [caspase-recruitment domain (CARD) membrane-associated guanylate kinase (MAGUK) protein 1] has a central role in regulation of NF-κB and the JNK2/c-Jun complex in both B and T lymphocytes. During last several years, the tremendous work has been done to reveal the mechanism by which CARMA1 and its signaling partners, Bcl10 (B cell CLL-lymphoma 10) and MALT1 (mucosa-associated lymphoid tissue 1), are activated and mediate NF-κB and JNK activation. In this review, we summarize our findings in revealing the roles of CARMA1 in the NF-κB and JNK signaling pathways in the context of recent advances in this field.